Secondary School Learners’ Transition to the University: A Qualitative Research Approach - Mbulaheni Paul Tshisikhawe; Buyisani Dube (E-Journal of Humanities, Arts and Social Sciences)
The transition of learners from secondary school to university education, while inevitable, has always been marred by myriad uncertainties and challenges. This is especially so for secondary school learners who register in previously disadvantaged higher education institutions. The purpose of this study was to explore the challenges experienced by first-year learners who transition from secondary school to university. The study followed a post-positivist methodological stance. A phenomenological design of the qualitative research approach was used in this research. The study adopted a purposive sampling technique to select two lecturers and ten first-year learners, who were interviewed using face-to-face and focus group interviews. The sample was drawn from the lecturers who taught first-year modules and all first-year learners in the school of education. Data was analysed and interpreted thematically. The study findings showed that challenges related to the orientation of learners, class attendance, language of teaching and learner support compromise the transition of first-year learners, a majority of who end up failing or dropping out of the university. This implies that learner integration and academic growth require supportive interaction with all stakeholders and the provision of resources and facilities. The study concludes that learners should be adequately prepared for the transition from secondary to university to enable them to cope with the social and academic demands of university life. The study has shown that the assumptions of Maslow’s hierarchy of needs theory can profitably be infused in learner transition thinking and practices to yield a successful university life.